Effect of microstructure and chemical proximate composition on mechanical properties of Procambarus clarkii shell. (1st August 2022) - Wang, Chao; Shi, Gangpeng; Que, Feng; Xia, Yuting; Li, Xuehong; Yang, Hao; Shi, Liu; Wu, Wenjin; Ding, Anzi; Li, Xin; Qiao, Yu; Liao, Li; et al.
Abstract: Procambarus clarkii was harvested in different months (April, May, and June) and classified to different groups based on weight (small, 10–20 g; medium, 20–30 g; and large, 30–40 g). The head shells (HS) and tail shells (TS) were obtained and chemical proximate components, microstructure and texture of crayfish shell were investigated, and the principal component analysis (PCA) and correlation analysis among the indices was performed. The results indicated that the moisture content of crayfish shell was significantly decreased ( P  < 0.05), whereas the contents of chitin, ash, and calcium was increased with the passage of sampling time and the increase of sampling weight. Under the same crayfish weight and same sampling month, the hardness and lipid content of HS were higher than TS, while the protein content exhibited an opposite trend. The results of PCA and correlation analysis showed that the gradual harden crayfish shell from April to June exhibited an increased thickness, ordered protein, tighten intramolecular and intermolecular hydrogen bonds, which might possess a high mechanical properties of red swamp crayfish during transport. This work would be benefit for the replenishment of crayfish shell database and provided theoretical references for crayfish transportation standard. Graphical abstract: Image 1 Highlights: The freshwater crayfish shell had a twisted plywood structure. The shell hardness was related to structural characteristics of crayfish shell. The main reason for hardening of shell was the ordered secondary structure.